2016
DOI: 10.1007/s10265-016-0880-6
|View full text |Cite
|
Sign up to set email alerts
|

Fading of wound-induced volatile release during Populus tremula leaf expansion

Abstract: The release of stress-driven volatiles throughout leaf development has been little studied. Therefore, we subjected poplar leaves during their developmental stage (from two days to two weeks old) to wounding by a single punch hole, and measured online the wound-induced volatile organic compound emissions. Our study shows that the emission of certain volatile compounds fades with increasing leaf age. Among these compounds we found lipoxygenase products (LOX products), acetaldehyde, methyl benzoate, methyl salic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 55 publications
(83 reference statements)
3
18
0
Order By: Relevance
“…To identify the signals of volatile products of the LOX pathway in the blend of parent and fragment masses detected by PTR‐TOF‐MS, pure chemicals (Sigma‐Aldrich, St. Louis, MO, USA) were individually analysed and mass signals consistent with previous studies were found (e.g. Brilli et al ; Portillo‐Estrada et al ). The total LOX product emission presented in this study is the sum of the dominant compounds with m / z of 81.070, 83.085, 85.101, 99.080, 101.096 and 143.107, representing 2‐hexenal and 3‐hexenal (C 6 H 10 O)H + , 3‐hexenol (C 6 H 12 O)H + , 1‐hexanol (C 6 H 14 O)H + , 3‐hexenol (C 6 H 12 O)H + and hexenyl acetate (C 8 H 14 O 2 )H + , respectively (Beauchamp et al ; Giacomuzzi et al ; Portillo‐Estrada et al ; Portillo‐Estrada et al ).…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…To identify the signals of volatile products of the LOX pathway in the blend of parent and fragment masses detected by PTR‐TOF‐MS, pure chemicals (Sigma‐Aldrich, St. Louis, MO, USA) were individually analysed and mass signals consistent with previous studies were found (e.g. Brilli et al ; Portillo‐Estrada et al ). The total LOX product emission presented in this study is the sum of the dominant compounds with m / z of 81.070, 83.085, 85.101, 99.080, 101.096 and 143.107, representing 2‐hexenal and 3‐hexenal (C 6 H 10 O)H + , 3‐hexenol (C 6 H 12 O)H + , 1‐hexanol (C 6 H 14 O)H + , 3‐hexenol (C 6 H 12 O)H + and hexenyl acetate (C 8 H 14 O 2 )H + , respectively (Beauchamp et al ; Giacomuzzi et al ; Portillo‐Estrada et al ; Portillo‐Estrada et al ).…”
Section: Methodsmentioning
confidence: 81%
“…Methanol and methyl salicylate (MeSA) were detected as the protonated parent ions at m / z of 33.034 and 153.088, respectively (Brilli et al ; Tasin, Cappellin, & Biasioli ; Maja et al ; Brilli et al ; Giacomuzzi et al ; Portillo‐Estrada et al ; Yener et al ; Portillo‐Estrada et al ). To identify the signals of volatile products of the LOX pathway in the blend of parent and fragment masses detected by PTR‐TOF‐MS, pure chemicals (Sigma‐Aldrich, St. Louis, MO, USA) were individually analysed and mass signals consistent with previous studies were found (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of methanol in the BVOC emission blend of poplar leaves is known (Hüve et al ., ). Methanol emission is related to cell elongation and division, and occurs more intensively in younger and expanding leaves (Brilli et al ., ; Portillo‐Estrada et al ., ), remarkably in early spring, even before isoprene is emitted (Ghirardo et al ., ). Therefore, a plantation of poplars, a fast‐growing species that quickly unfolds its leaves in spring, generates a burst of methanol emission due to the many young and expanding leaves during this period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a temporal lag between isoprene emission and the onset of photosynthesis (Kuzma & Fall, ; Sharkey & Loreto, ; Monson et al ., ). Leaf phenology plays an important role in determining the level of isoprene emissions (Brilli et al ., ; Portillo‐Estrada et al ., ). Isoprene emission rates differ among different species of the same genus, or among genotypes of the same species, as already documented in Populus (Calfapietra et al ., ).…”
Section: Introductionmentioning
confidence: 97%